Government‐led innovation acceleration: Case studies of US federal government innovation and technology acceleration organizations. - Roberts, Patrick S.; Schmid, Jon (Review of Policy Research, 2022)
How can agencies that have operational activities as a primary focus improve the procurement and transition of innovative technologies, particularly from the private sector? This study seeks to inform scholars and public‐sector managers about organizational design for innovation and technology acceleration using a systems approach. It examines three organizations responsible for mission‐oriented innovation: In‐Q‐Tel, stood by up the Central Intelligence Agency; the FBI's Operational Technology Unit; and the National Institute for Occupational Safety and Health (NIOSH). It finds that collaboration and mission‐inspiration can bridge public–private sector divides, but that distance from operators can slow technology adoption. It recommends establishing metrics for innovation investments and outcomes and gaining a better understanding of end user needs. Venture capital characteristics in quasi‐government innovation organizations show promise but are untested outside of defense and intelligence. This study contributes to the literature by analyzing technology acceleration rather than initiation, development, adoption, or diffusion. It also adds to the study of technology acceleration in mission‐oriented agencies that are less often the focus of R&D scholarship on big science.